Chemical residue coming forward in an end product in winery technology - Nyers, Tamás (Acta Agraria Debreceniensis, 2008)
Although many tasks wait for me yet in the course of my research work, I’ve managed to book successes with a certain degree. On the one part as a producer I regard it as a positive result, that in the capital end product manufactured by me, - that is the wine - , has no chemical residue in it, and in the rest of the intermediary products has measure dwindling only. On the other hand, that I hit home in cases demonstrable agent residual one in the must, wine, lees, the tendency indicates it, that in the course of the processing (distillation) or the storage they partly, or whole decay (Table 4. and Figure 3.) and a food safety risk is not caused. But it’s a question for the future, that the more considerable quantity manifested in the grape pip does or not cause a problem in the course of its use with a cosmetic aim, concerned, that the reason of the agent wandering experienced in the other products is the relative density, or possibly the result of some kind of bond. So I go on with my research and my aim is to gove the most exact answers for those questions, above.